Efek Alelopati Ekstrak Air Daun Mangga (Mangifera indica L. Var. Arumanis) Terhadap Pertumbuhan Rumput Teki (Cyperus rotundus L.) - Davina Nathania Prasetya; Zulkifli Zulkifli; Tundjung Tripeni Handayani; Martha L. Lande (Politeknik Negeri Lampung., 2018)
The purpose of this research is to know whether the aqueous extract of mango leaves(Mangifera indica L.) affect the growth of purple nutsedge (Cyperus rotundus L.). Thisresearch conducted at Botanical Laboratory of Biology Department Faculty of Mathematicsand the Natural Sciences University of Lampung from September to October 2017. Thisexperiments were carried out in a complete randomized design with the main factors beingaqueous extract of mango leaves with 5 level concentration : 0% w / v ( control), 5% w / v,10% w / v, 15% w / v, and 20% w / v and consist of 5 replications. Parameters measuredwere shoot length, fresh weight, dry weight, and relative water content. The Levene testdetermined the homogeneity of variance at 5% significant level. Analysis of variance andTukey HSD testis did at 5% significant level. The results showed that the concentration ofextract was negatively correlated with shoot length where the shoot length was decreasedsignificantly at 20% extract concentration. Total fresh weight was decreased significantly at20% and correlated linearly negative with extract concentration. Total dry weight wasdecreased significantly at 20% extract concentration. There was no significant effect onrelative water content. From this research, it concluded that aqueous extract of mangoleaves at 20% extract concentration was decreased shoot length, fresh weight and dry weightof purple nutsedge.